Fios e desafios da atenção à saúde da criança no Estado do Espírito Santo : análise da mortalidade de zero a cinco anos com gestores do Programa Estadual de Saúde da Mulher e da Criança - Santos, Tânia Mara Ribeiro dos (2013)
This is a qualitative study aiming to discuss the children mortality from zero to five years old of Espírito Santo state, Brazil. The documental research was realized in the period comprehended between August 2011 to August 2012 using articles published by a daily newspaper of large circulation printed media, namely "A Gazeta". The articles have been arranged in a newspaper library that supported the creation of a panel reprographic. The research subjects were the technicians who make up the Coordination staff of State Program on Women and Children's Health. The production of study material was made from the analysis of a focal group using a semi-structured road map and taking as starting analyzing a copy of the panel and its materials. All material was recorded and filmed. The Analysis Institutional was the beacon guiding to the entire formulation and study description. As recommends this theoretical framework proposed by Lourau, the final step of the project consisted in a refund concrete as a part of a scientific procedure to improves the discussion of the productions in research with stakeholders to enable their direct interference in this process. The study proves two results. At first, the subjects were able to reflect on how much is needed pursue a dialogue with other sectors considering the natural analyzer that is the death of children under five years. On the other hand the institutional analysis, with its power to provoke self-analysis and self-management, gave them a chance to rethink their work processes in child health care.